Textbook Analysis of 'Basic English for Tourism' using Tomlinson’s Theory - Abdul Syahid; Ayu Sundari; Maulidina Tri Amanda; Rani Oktavia (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This study analyzes the textbook "Basic English for Tourism" based on Tomlinson's criteria and Littlejohn's Three Levels of Analysis. The findings show that the textbook fulfills several important criteria for effective language learning, such as providing relevant and practical materials, improving language confidence and fluency, and incorporating various learning methods. The book offers a variety of activities, including dialogs, text analysis, writing tasks and grammar lessons, which suit different learning styles and encourage interactive and communicative language use. Although the absence of pictures may be considered a limitation, the content and overall approach of this textbook make a significant contribution in improving English language skills for students in the tourism industry. Therefore, this study provides valuable insights for practitioners and policy makers in the field of English language education, emphasizing the importance of selecting textbooks that match the practical needs and learning objectives of the students.